Studies on Pine Oleoresin Part I : Resin Acid Compositions - Panda, Rakhishinda; Panda, Himadri (Indian Forester, 1986)
The resin acid compositions of some Indian Pine oleoresin like Pinus taeda, Pinus Patula, Pinus caribaea, Pinus psuedostrobus Pinus yunnaenss, Pinus massoniana, Pinus kesiya, Pinus Elliottii, Pinus cubensis, Pinus griffithii, Pinus douglasiana, Pinus Merkusii, Pinus Gerardiana, Pinus armandi,Pinus bungeana and Pinus roxburghii are reported. The data indicates that the source of some oleoresins can be identified by their composition.